Rituals online: transferring and designing rituals - Radde-Antweiler, Kerstin (Online - Heidelberg journal of religions on the internet, 2006)
Kerstin Radde-Antweiler stresses the aspect of ritual construction by the individual believers in her paper Rituals Online. Transferring and Designing Rituals. In addition to the potential of the Internet to offer interaction and new processes of communication in the context of rituals – the so called "Online-Rituals" –, this medium also offers much information about rituals and instructions how to perform a ritual, in and outside the Internet. This varies from the publication of – at first glance - fixed ritual prescripts to texts on how to design a ritual by him- or herself. These fixed texts are often identified as old traditional scripts, whereas critical analyses show explicit or implicit transfers and receptions of various religious traditions. In the paper, different ritual prescripts presented on Wicca- and Solitaire Homepages, which are often seen as continuation of pre-Christian, matriarchal, Celtic and Germanic cults and mythologies, are analysed and their transfer processes are exemplified. Instances that show the processes of ritual transfer are the choice of the owner-names, the mixture of deities of different religions, the integration of different feasts and festivals etc. The assertion of perpetual continuity from the insider perspective seems contradict those texts which encourage the believers to develop their own individual ritual. Therefore, the elements of newness and invention as well as the phenomenon of Ritual Design in their processes of gaining legitimacy and authority has to be examined.